Beyond Coherent Oxide Heterostructures: Atomic‐Scale Structure of Misfit Dislocations. Issue 9 (24th June 2019) - Dholabhai, Pratik P.; Uberuaga, Blas P.
Abstract: Nanoscale design of complex oxide heterostructures and thin films is imperative as they have significant promise in novel technological applications. A coherent interface is formed in oxide heterostructures with small mismatches, and the lattice mismatch is completely compensated by elastic strain. In semi‐coherent oxide heterostructures, when an epitaxial layer is grown on the substrate above the critical thickness of the film, misfit dislocations are formed to mitigate the strain between the two materials with dissimilar lattice constants. Key properties of semi‐coherent oxide heterostructures are influenced or even controlled by the presence of misfit dislocations. Therefore, it is critical to understand the atomic‐scale structure of semi‐coherent oxide heterostructures, specifically the structure of misfit dislocations that are ubiquitous at such heterointerfaces. Numerous state‐of‐the‐art experiments have reported emergent phenomena at semi‐coherent oxide heterostructures, wherein misfit dislocations play a crucial role. However, their atomic‐scale and nanoscale structure is not always discernable from experiments. Due to large system sizes, computational studies dedicated to examining misfit dislocations in semi‐coherent oxide heterostructures are still in their infancy. This review aims to summarize the recent advancements and challenges involved in computational studies elucidating the atomic‐scale structure of misfit dislocations in semi‐coherent oxide heterostructures and motivate future computational efforts. Abstract : Key properties of semi‐coherent complex oxide heterostructures and thin films are influenced by the presence of misfit dislocations at the interface. This review sheds light on the recent advancements in computational studies focused on disentangling the atomic‐scale structure of misfit dislocations, leading to a discussion of current challenges and potential future pathways for computational approaches in the field.